Partial gene duplication in Duchenne and Becker muscular dystrophies. Issue 6 (June 1988) - Hu, X Y; Burghes, A H; Ray, P N; Thompson, M W; Murphy, E G; Worton, R G
Abstract : Duchenne and Becker muscular dystrophies (DMD and BMD) are progressive muscle wasting disorders with an X linked recessive mode of inheritance. We have surveyed 120 unrelated patients with DMD or BMD for gene duplications using a series of genomic probes from within the DMD/BMD gene locus. In three patients, two with DMD and one with BMD, a duplicated region within the DMD/BMD locus has been shown by Southern blot analysis and transmission densitometry. In two cases a new restriction fragment spanning the duplication junction has been visualised, indicating that the duplications are tandemly arranged. Mendelian inheritance of the duplication has been shown in two families by following the segregation of the duplication junction fragment. The three duplication cases have been analysed with a cDNA probe isolated from the DXS206 region of the DMD/BMD locus and the duplication of a specific set of exons has been found in two cases. This study shows that all three duplications are internal to the gene and confirms that such a duplication can result in a genetic disorder through the disruption of exon organisation.